High prevalence of epilepsy in two rural onchocerciasis endemic villages in the Mahenge area, Tanzania, after 20 years of community directed treatment with ivermectin - Bruno P. Mmbando; Patrick Suykerbuyk; Mohamed Mnacho; Advocatus Kakorozya; William Matuja; Adam Hendy; Helena Greter; Williams H. Makunde; Robert Colebunders (BMC, 2018)
Abstract Background Epilepsy is a neurological disorder with a multitude of underlying causes, which may include infection with Onchocerca volvulus, the parasitic worm that causes human onchocerciasis. A survey carried out in 1989 revealed a high prevalence of epilepsy (1.02% overall, ranging from 0.51 to 3.71% in ten villages) in the Mahenge area of Ulanga district, an onchocerciasis endemic region in south eastern Tanzania. This study aimed to determine the prevalence and incidence of epilepsy following 20 years of onchocerciasis control through annual community directed treatment with ivermectin (CDTI). Methods The study was conducted in January 2017 in two suburban and two rural villages in the Mahenge area. Door-to-door household visits were carried out by trained community health workers and data assistants to screen for persons suspected of having epilepsy, using a standardised questionnaire. Persons with suspected epilepsy were then interviewed and examined by a neurologist for case verification. Onchocerciasis associated epilepsy was defined as epilepsy without an obvious cause, with an onset of seizures between the ages of 3-18 years in previously healthy children. In each village, fifty males aged ≥20 years were tested for onchocerciasis antibodies using an OV16 rapid test and were examined for presence of onchocerciasis nodules. Children aged 6-10 years were also tested using OV16 tests. Results 5117 individuals (median age 18.5 years, 53.2% female) from 1168 households were screened. 244 (4.8%) were suspected of having epilepsy and invited for neurological assessment. Prevalence of epilepsy was 2.5%, with the rural villages having the highest rate (3.5% vs 1.5%), P < 0.001. Overall incidence of epilepsy was 111 cases (95% CI: 73-161) per 100 000 person-years, while that of onchocerciasis associated epilepsy was 131 (95% CI: 70-223). Prevalence of OV16 antibodies in adult males and among children 6-10 years old was higher in rural villages than in suburban villages (76.5% vs 50.6, and 42.6% vs 4.7% respectively), (P < 0.001), while overall prevalence of onchocerciasis nodules was 1.8%. Conclusions This survey revealed a high prevalence and incidence of epilepsy in two rural onchocerciasis endemic villages in the Mahenge area. Despite 20 years of CDTI, a high prevalence of OV16 antibodies in children aged 6-10 years suggests on-going O. volvulus transmission. Reasons for the persistence of on-going parasite transmission in the Mahenge area need to be investigated.